The Relationship between Pregnancy Exercise and the Level of Anxiety of Pregnant Women in Confronting Normal Childbirth at the Kartasura Health Center Work Area - Putri Nurlia Anggraini; Sulastri Sulastri (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
The first of the psychological issues that pregnant women frequently face, particularly during the third trimester, is anxiety related to typical labor. Pregnancy exercises are among the non-pharmacological strategies that can be used to lessen anxiety. The purpose of this study is to ascertain how pregnant women's anxiety levels at the Kartasura Health Center working area relate to their prenatal exercise regimens. This study employed a cross-sectional design and a quantitative methodology. The research was conducted in the working area of the Kartasura Health Center which was carried out in August 2024. The population of this study were all third trimester pregnant women in the Kartasura Health Center area as many as 258. The sample technique used purposive sampling so that the sample in this study was 72. Data collection for this study used demographic questionnaires and PASS (Perinatal Anxiety Screening Scale) anxiety questionnaires. Data analysis in this study with Descriptive Univariate and Bivariate analysis with Chi-Square test. The results showed that pregnant gymnastics has a relationship with reducing anxiety and smoothness in facing the normal labor process at the Kartasura Health Center (p-value-0.036). It is expected that medical professionals can increase the pregnant exercise program and reduce maternal morbidity. Pregnant exercises can be included in the childbirth preparation program at the Kartasura Health Center to help pregnant women face childbirth more calmly. Keywords: Pregnancy Exercise, Anxiety, Third Trimester Pregnant Women